Fluid boundaries : forming and transforming identity in Nepal - Fisher, William F., 1951- (Columbia University Press, 2001)
Examining the relationship between societal practice, historical processes, and culture in a Nepali society, this book tells the story of the Thakali's search for identity and their efforts to clarify and represent their culture and history.